Dysmenorrhea in a multiethnic population of adolescent Asian girls - Wong, L.P.; Khoo, E.M. (Elsevier, 2010)
Objective: To determine the prevalence of dysmenorrhea, its impact, and the treatment-seeking behavior of adolescent Asian girls. Method: A cross-sectional study with 1092 girls from 15 public secondary schools and 3 ethnic groups in the Federal Territory of Kuala Lumpur, Malaysia. Results: Overall, 74.5 of the girls who had reached menarche had dysmenorrhea; 51.7 of these girls reported that it affected their concentration in class; 50.2 that it restricted their social activities; 21.5 that it caused them to miss school; and 12.0 that it caused poor school performance. Ethnicity and form at school were significantly associated with the poor concentration, absenteeism, and restriction of social and recreational activities attributed to dysmenorrhea. Only 12.0 had consulted a physician, and 53.3 did nothing about their conditions. There were ethnic differences in the prevalence, impact, and management of dysmenorrhea. Conclusion: There is a need for culture-specific education regarding menstruation-related conditions in the school curriculum. (C) 2009 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.